2006
DOI: 10.1038/sj.jhh.1002030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cilnidipine on left ventricular function in hypertensive patients as assessed by tissue Doppler Tei index

Abstract: Tissue Doppler Tei index is pointed to be more effective in the evaluation of global cardiac function than systolic and diastolic measurements alone in various heart diseases. This study was designed to assess the effect of cilnidipine on left ventricular function in hypertensive patients by using this index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Support for such a conclusion came from previous studies that showed that although the ejection fraction was similar among different patient groups, Sm was different [4,20,22].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Support for such a conclusion came from previous studies that showed that although the ejection fraction was similar among different patient groups, Sm was different [4,20,22].…”
Section: Discussionsupporting
confidence: 52%
“…Systemic hypertension is one of the most important causes of pathological LVH. The presence of hypertension or LVH may affect cardiac function not only by impairing myocardial function [4], but also by disturbing the coordination between regions of the ventricle, resulting in ineffective contraction [5].…”
mentioning
confidence: 99%
“…Clinical studies have indicated that depressed LV systolic function and impaired diastolic function often co-exist in hypertensive patients (1,4,22), and LV synchronicity is impaired in hypertensive patients (6). Hypertension and cardiac arrhythmias co-exist in many patients, and the most important promoter of ventricular arrhythmogenesis in hyper- tensives is LV hypertrophy (7,8,23).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hypertension may affect cardiac function not only by impairing myocardial function (4,5), but also by disturbing the coordination between regions of the ventricle, resulting in ineffective contractions (6). Hypertension and ventricular arrhythmias coexist in many patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hypertension may affect the cardiac function not only by impairing myocardial function [2], but also by disturbing the coordination between regions of the ventricles, resulting in ineffective contraction and relaxation [3,4]. In addition to that, the presence of left ventricular (LV) dyssynchrony is not uncommon in hypertension [4].…”
Section: Introductionmentioning
confidence: 99%